PORTFOLIO OF RESEARCH PROJECTS AS A PREROGATIVE OF UNIVERSITIES TO ENSURE FINANCIAL AUTONOMY - Bohashko, Oleksandr; Bohashko, Iryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The growing role of higher education in modern society and the expansion of the boundaries of science require a change in the models of university funding through the integration of certain corporate governance mechanisms. Of particular importance is the ability of universities to attract funding, including from private sources, by combining basic and applied research. It is critical for universities to find an optimal balance between basic and applied research when making decisions on launching new projects and programmes or adjusting existing ones.The purpose of the article is to determine the peculiarities of forming a balanced portfolio of research projects to ensure the financial autonomy of modern universities.The scientific research uses general scientific and special methods, in particular: analysis and synthesis; comparison, systematisation and generalisation, and the graphical method to clearly present the theoretical and practical provisions of the scientific article.The proposed approaches to assessing the university's portfolio of technological innovation developments will contribute to the efficient use of limited resources, prioritisation, risk analysis and monitoring of results in the short and long term. This will create a network of partners to share knowledge, research and resources.